PENGARUH UKURAN PERUSAHAAN, LEVERAGE, DAN KOMITE AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2016-2020 - Jefri Antoni Rajaguk-guk (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Previous studies have found that various factors such as company size, leverage, and audit committee can influence companies to immediately submit their financial statements or delay the delivery time. So that this delay in delivery results in the benefits of the information being conveyed being reduced and causing information asymmetry. However, existing studies still show varying results so they want to know more about the Effect of Company Size, Leverage, and Audit Committee on Audit Delay in Property and Real Estate Companies Listed on the Indonesia Stock Exchange. This research is a type of quantitative research. The type of data used in this study is secondary data in the form of financial statements, especially balance sheets and audited reports. The population in this study are property and real estate companies on the IDX for the 2016-2020 period. The study found that property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020, it can be said that company size has a significant positive effect on audit delay, leverage does not have a significant positive effect on audit delay, and the audit committee has a significant positive effect on audit delay. significant negative effect on audit delay.